Transverse emittance measurement in the CERN Proton Synchrotron in view of beam production for the High-Luminosity LHC. (November 2019) - Senes, E; Emery, J; Fraser, M A; Guerrero Ollacarizqueta, A; Huschauer, A; Roncarolo, F; Sirvent, J L; Skowronski, P; Tecker, F; Forte, V
Abstract: In the framework of the LHC Injectors Upgrade project the improvements required to achieve the parameters of the future beams for the High-Luminosity LHC are being studied and implemented. In order to deliver high brightness beams, control over the beam intensity and emittance is fundamental. Therefore, a highly accurate and reliable transverse emittance measurement is essential. Presently at the CERN Proton Synchrotron, the only operationally available emittance monitors not impacting the facility beam production are the flying wire scanners used to measure the circulating beam profile. The wire scanners will be replaced with a new generation in the next two years and a prototype is already installed. The prototype has been commissioned with beams featuring a wide range of intensities and emittances. This paper evaluates the performance of the prototype with respect to the present system via beam-based measurements. The transverse emittance measurement is discussed, considering the different potential error contributions to the measurement, such as knowledge of the machine optics and the dispersive contribution to the beam size.